PERAN PEMERINTAH DESA DALAM MENANGANI ANAK PUTUS SEKOLAH DI DESA BABAKAN KARET - Rachmat Rachmat; Neli Yuliawati; Yasinta Nursawali (Sawala Cendikia : Jurnal Penelitian Multidisiplin, 2025)
This study aims to analyze the role of the village government in addressing the issue of school dropouts in Babakankaret Village, Cianjur District, Cianjur Regency. A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, observation, and documentation, involving key informants such as village officials, teachers, parents, and school dropouts. Data analysis was conducted using data reduction, data display, and conclusion drawing, while validity was ensured through triangulation techniques. The findings reveal that the village government has performed its roles as a facilitator, regulator, and catalyst through the implementation of non-formal education programs, provision of educational assistance, and community awareness initiatives regarding the importance of education. However, these efforts have not yet been fully effective due to several constraints, including economic limitations, low educational awareness, inadequate infrastructure, and socio-cultural factors. The implementation of educational acceleration programs has shown positive impacts, yet it has not comprehensively reached all school-age children who have dropped out. This study concludes that the role of the village government in addressing school dropout issues remains suboptimal and requires stronger policy support, improved coordination, and greater community participation to ensure more effective and sustainable outcomes.